Building Climate Resilient Agriculture in Caribbean Countries: Belize - Hayman, Alicia (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Belize's Initial Nationally Determined Contribution (NDC) did not include agriculture in its mitigation targets, but it was identified as a priority sector for adaptation measures. However, implementing climate resilient agriculture (CRA) faces barriers such as a financing gap, lack of data, resource constraints, weak institutional capacity, and uncertain land tenure. Despite this, opportunities exist to build CRA and enhance climate ambition in NDCs by focusing on significant emission sources, promoting domestic growth of higher quality forage, establishing anaerobic digesters, and exploring measures beyond the farmgate.